Analysis of Multicultural Education Model Based on Islamic Values ​​in Madrasah Ibtidaiyah: Study of Curriculum Design and Learning Practices - Umami, Novia Rizqiatul; Yani, Ahmad; Kambali, Kambali (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2025)
This study aims to describe teachers' perceptions of multicultural education and Islamic values, integration of multicultural curriculum in the learning process, implementation of Islamic values ​​in daily learning, challenges faced, and innovations and expectations of teachers in implementing them. The research method uses qualitative descriptive, the research location is at MI Al Washliyah Perbutulan, Cirebon Regency. Data were collected through in-depth interviews, data analysis techniques used were data reduction, data presentation, and drawing conclusions. The results showed that multicultural education is closely related to Islamic values, such as tolerance, justice, and brotherhood, which support and complement each other. The integration of these values ​​is reflected in learning activities and extracurricular activities at school, such as cultural visits, local art exhibitions, and the implementation of social activities that encourage students to live side by side in harmony. The curriculum implemented at MI Al Washliyah Perbutulan integrates multicultural values ​​into the school's vision and educational goals, which are formulated in curriculum documents and in daily practices. In addition, the application of Islamic values ​​in learning, such as rahmah (compassion), tasamuh (tolerance), and 'adl (justice), is also applied in school activities to create an inclusive and just environment. However, challenges in implementing multicultural education still exist, especially related to limited resources, teacher understanding, and resistance to change. This study concludes that multicultural education based on Islamic teachings can create a harmonious, tolerant, and inclusive environment at MI Al Washliyah Perbutulan, by integrating local culture and social values ​​into the curriculum implemented.